Injuries and Illness in Elite Equestrian Athletes: A Two-Season Prospective Study - Lang, M.; Moen, M. H.; van Roy, T.; Verhagen, E. (Deutsche Zeitschrift für Sportmedizin, 2021)
Problem/Intro: Epidemiological data of injuries and illnesses in equestrian athletes are limited. The objective of this study was to describe the incidence, prevalence, and severity of health problems among a cohort of elite riders.